Combined Print and Skillbeck situation analysis model toward the development of an extension program - Cabling, Kristine A. (College of Education, University of the Philippines Diliman, 2019)
This study focuses on the operationalization of Print's (1993) model of situation analysis with the use of Skillbeck's (Reynolds & Skillbeck, 1976) factors in the context of implementing the procedure as an initial step in curriculum development. Due to the gap in literature in implementing situation analysis, the purpose of this research is threefold: to contribute to the field of curriculum studies, particularly curriculum planning, by providing information and and guidance in implementing situation analysis; to improve teachers, administrators, and curriculum workers in the country by giving them tools to make information-driven decisions about the curriculum; and to simulate improvement in the locale wherein this study was conducted. Print (1993) four-step model was modified to remove the third step of collecting and analyzing data to incorporate it throughout the whole procedure. This resulted in the following steps to conduct situation analysis; identifying problems in context, selecting appropriate factors, and making recommendations. In order to accomplish the first step, data were gathered from the participants about the relationship of each factor with each element of the curriculum through a survey, a focus group discussion, and interviews. The second step was carried out by assigning the appropriate factors and dimensions to the issues that emerged from the previous step. Finally, taking into consideration the problems of the curriculum and their underlying factors, recommendations were made to resolve the problems. Doing this study revealed that for the initial situation analysis, it is necessary that each step should be anchored in literature and that the first step is crucial given that its results will determine the results of the subsequent steps. Further studies could expand on the dimensions of each factor and add to the methods of conducting each step of situation analysis.